KAJIAN FITOKIMIA Hopea mengarawan DAN IMPLIKASINYA PADA KEMOTAKSONOMI HOPEA - Sahidin Sahidin; EuisH Hakini; Yana M Syah; Lia D Juliawaty; Sjamsul A. Achmad; Laily Bin Din; Jalifah Latip (BERITA BIOLOGI, 2006)
Nine resveratrol oligomers have been isolated from the stem bark of Hopea mengarawan i.e. diptoindonesin D (1), balanocarpol (2), ampelopsin A (3), hopeaphuran (4), heimiol A (5), parviflorol (6), a-viniferin (7), isohopeaphenol (8), and vaticanol B (9).The structures of these compounds were determined based on spectroscopic evidence such as UV, IR, 1-D, 2-D NMR and comparison with the reported data. Those compounds implied that Hopea tends to produce resveratrol dimers. Moreover, in subgenus level, besides ampelopsin A (3) and isohopeaphenol (9), resveratrol oligomers in H. mengarawan the same as in H.dryobalanoides. It indicated that H. mengarawan and H. dryobalanoid.es came from the same subgenus.